P08.25 Tubal factor infertility (tfi) epidemiology in infertility clinic patients. (13th September 2015) - Gorwitz, RJ; Hammond, KR; Wiesenfeld, HC; Cataldo, NA; Sereday, KA; Kissin, DM; Balmir, F; Haggerty, CL; Hook, EW; Steinkampf, MP; Markowitz, L; Geisler, WM
Abstract : Introduction: Prevention of tubal factor infertility (TFI) is a primary objective of chlamydia prevention programs. This study aimed to describe TFI epidemiology in infertility clinic patients. Methods: Data were analysed from one site of an ongoing two-site study. Medical record data from infertile (unable to conceive for ≥12 months, no history of tubal sterilisation) women aged 19–42 yrs with an initial consultation at a private infertility practice in Birmingham, Alabama during 01/01/2011–06/30/2012 were abstracted to a standardised form. TFI was defined by report of fallopian tube occlusion on hysterosalpingogram, hydrosalpinx on pelvic ultrasound, and/or evidence of fallopian tube damage (e.g., tubal occlusion, hydrosalpinx, peritubal adhesions) on laparoscopy. Statistical tests were used to compare proportions (Fisher's exact, chi-square) and medians (Wilcoxon). Results: Eligible patients (N = 413, median age 31 yrs) included 87 black, 303 white and 23 other race women, who had been trying to conceive a median of 30 months (48 months black vs 24 months white, p < 0.001) at initial consultation. Recorded history of chlamydia and pelvic inflammatory disease (PID) were more common in black than white patients (9.2% vs 1.3%, p = 0.001; 6.9% vs 1.6%, p = 0.02). TFI was identified in 82 (19.9%) women (32.2% black vs 15.8% white, p < 0.001). Among 82 women with and 331 without TFI, a history of chlamydia was recorded in 2.4% vs 3.3% (p = 1.0), gonorrhoea in 0% vs 1.2% (p = 1.0), PID in 6.1% vs 1.8% (p = 0.047), and ectopic pregnancy in 14.6% vs 2.4% (p < 0.001). Conclusion: TFI was identified in one-fifth of infertility patients. Black women had been attempting to conceive longer before initial consultation than white women, and had a higher prevalence of TFI. Known sexually transmitted infection (STI) history was uncommon, but more prevalent in blacks. Studies using biological measures of exposure (e.g., serology) are needed to better define the proportion of TFI attributable to STIs.